Mass Dispersal of Terrestrial Organisms During First Flush Events in a Temporary Stream. (7th August 2014) - Rosado, J.; Morais, M.; Tockner, K.
Abstract Temporary streams expand and contract seasonally, forming a complex mosaic of aquatic, amphibic and terrestrial habitats. We studied the terrestrial arthropod fauna at the surface of the dry river bed as well as the fauna of Coarse Particulate Organic Matter (CPOM) deposits 0, 5 and 10 days after first flush events (years 2004–2006) along the Pardiela stream (SE Portugal). During the dry period, large amounts of organic material accumulated at the surface of the dry bed, colonized by abundant terrestrial arthropods (mean density: 13.3 ± 15.29 Ind g DM (Dry Mass of CPOM)). Arthropod density peaked in fresh flood deposits (mean density: 35.8 ± 33.4 Ind g DM), and subsequently decreased within time. Concurrently, the relative composition of the arthropod community changed from Day 0 to Day 10. The present results demonstrated that the dry bed of temporary streams served as a major habitat for terrestrial arthropods. During the first flush events, a mass dispersal of terrestrial arthropods, rafting on floating CPOM, occurred, subsequently forming distinct deposits along the channel margin. These deposits may constitute critical habitats, refugia and food resources for local and regional terrestrial arthropod assemblages. Copyright © 2014 John Wiley & Sons, Ltd.